Vibrotactile enhancement in hand rehabilitation has a reinforcing effect on sensorimotor brain activities - Du, Qiang; Luo, Jingjing; Cheng, Qiying; Wang, Youhao; Guo, Shijie (Frontiers in Neuroscience, 2022)
Objective: Stroke patients often suffer from hand disfunction or lose of tactile perception, which in turn interferes with hand rehabilitation. Tactile-enhanced multi-sensory feedback rehabilitation is an approach worth considering, but its effectiveness has not been well studied. By using functional near-infrared spectroscopy to analyze the causal activity patterns in the sensorimotor cortex, the present study aims to investigate the cortical hemodynamic effects of hand rehabilitation training when tactile stimulation is applied, and to provide a basis for rehabilitation program development. Methods: A vibrotactile enhanced pneumatically-actuated hand rehabilitation device was tested on the less-preferred hand of 14 healthy right-handed subjects. The training tasks consisted of move hand and observe video (MO), move hand and vibration stimulation (MV), Move hand, Observe video, and Vibration stimulation (MOV), and a contrast resting task. Region of interest, a laterality index, and causal brain network analysis methods were used to explore the brain’s cortical blood flow response to a multi-sensory feedback rehabilitation task from multiple perspectives. Results: 1) A more pronounced contralateral activation in the right-brain region occurred under the MOV stimulation. Rehabilitation tasks containing vibrotactile enhancement (MV, MOV) had significantly more oxyhemoglobin than the MO task at 5s after the task starts, indicating faster contralateral activation in sensorimotor brain regions. 2) Lateralization (p<0.05) was produced by 41.7% of pairs of channel sets under MV, MOV task, respectively, MO produced 16.7% and Rest did not, showing that MV, MOV caused stronger lateralization activation. 3) We investigated all thresholds of granger causality (GC) resulting consistent relative numbers of effect connections. MV elicited stronger causal interactions between the left and right cerebral hemispheres, and at the GC threshold of 0.4, there were 13 causal network connection pairs for MV, 7 for MO, and 9 for MOV. Conclusions: Vibrotactile cutaneous stimulation as a tactile enhancement can produce a stronger stimulation of the brain’s sensorimotor brain areas, promoting the establishment of neural pathways, and causing a richer effect between the left and right cerebral hemispheres. The combination of kinesthetic, vibrotactile, and visual stimulation can achieve a more prominent training efficiency from the perspective of functional cerebral hemodynamics